HUBUNGAN KECERDASAN ADVERSITY DAN MOTIVASI BELAJAR TERHADAP PRESTASI AKADEMIK (Survey pada Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Siliwangi Angkatan 2020) - Shopa Jamiatul Hasanah; Yoni Hermawan; Ai Nur Solihat (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Students face various academic challenges, such as difficulties in understanding the material, exam pressure, and the transition from online to offline learning, which can hinder academic achievement. This study aims to identify the relationship between adversity quotient and learning motivation on students' academic achievement. The research method used is quantitative with an explanatory survey design. The population in this study consists of students from the Faculty of Teacher Training and Education at Siliwangi University, class of 2020, with a sample of 305 students selected using a random sampling technique. The data collection instrument was a questionnaire, and data analysis was conducted using the Spearman Rank correlation. The results indicate that both adversity quotient and learning motivation have a positive and significant relationship with academic achievement. This study provides practical implications for the development of educational programs aimed at enhancing adversity intelligence and learning motivation to support students' academic achievement.